(untitled) (Journal of Agriculture & Rural Development, 2010)
Effect of duckweed supplementation as fish feed to polyculture system was investigated. Fish were reared for 90 days with or without duckweed supplementation. The ponds were fertilized with cowdung, urea and triple super phosphate. All the important physico-chemical factors including temperature, transparency, dissolved oxygen, total alkalinity, phosphate-phosphorus and nitrate-nitrogen were within productive ranges for fish culture. Ponds were stocked with silver carp, Thai sharputui, tilapia, common carp and mrigel. After a 90 days rearing period, net fish production was found to be significantly higher in fish fed duckweed at a rate of 20% of body weight compared to fish without duckweed supplement. It was concluded that duckweed can effectively be used as feed for polyculture of fish. Key words: Duckweed; polyculture; feed. DOI: 10.3329/jard.v7i1.4437 J Agric Rural Dev 7(1&2), 157-160, June 2009